The U.P. President's end-of-term report, 1993-1999. - University of the Philippines System ([Quezon City] [University of the Philippines], 1999)
"Under the direction of the UP President, this 9 volume UP President's End-of-Term Report, covering the period 6 August 1993 to 5 August 1999, was prepared by the Office of the Vice President for Public Affairs in collaboration with the UP System Information Office; the Offices of the Vice Presidents for Academic Affairs, Finance and Administration, Planning and Development, and Information and Communication Systems; the Office of the Secretary of the University and the Office of Legal Services; the Offices of the Chancellors of all the UP autonomous universities; the Directors of the various System Offices, Centers, and Programs; and the Chairs of various Systemwide Committees for special programs and projects.
v.1. The U.P. President's report -- v.2. The Chancellors' reports : Diliman, Manila -- v.3. The Chancellors' reports : Los Banos, Visayas, Open University, Mindanao -- v.4. Admission, academic programs, & linkages -- v.5. Research, publications, & creative work -- v.6. Extension, voluntarism & public affairs -- v.7. Infrastructure development, resource generation & modernization -- v.8. Selected speeches of Emil Q. Javier, 17th U.P. President -- v.9. The U.P. centennial plan 2008.
Keywords: University of the Philippines -- Administration; University of the Philippines -- Presidents; University of the Philippines. -- Office of the President